Genetic analyses and molecular associations of FSHR and GH genes for semen traits in Egyptian buffalo - Abdelfatah R. Zaghloul; Maher H. Khalil; Mahmoud M. Iraqi; Amin M. S. Amin; Ibrahim Abousoliman; Ayman G. EL Nagar (BMC Veterinary Research)
Abstract Background & objectives The reproductive efficiency of buffalo bulls is crucial for genetic improvement, herd fertility, and overall productivity. Identifying genetic markers linked to semen traits can thus enhance breeding programs and optimize artificial insemination strategies. The objectives of this study were to estimate variance components and heritability. estimating the breeding values (EBVs), plotting the genetic and phenotypic trends and detection of the molecular genetic associations of FSHR and GH genes using PCR–RFLP with semen traits comprising ejaculate volume (EV), sperms motility (SM), live sperms (LS), abnormal sperms (AS) and sperms concentration (SC) in Egyptian buffalo. Methods Data of 5178 semen ejaculates were collected from 2013 to 2022 from 111 bulls, progeny of 34 sires and 92 dams in two experimental herds. For molecular genetic analysis, a total of 86 buffalo bulls were used to characterize FSHR and GH genes. Results The heritabilities estimates for semen traits were low and moderate, being 0.17, 0.28, 0.27, 0.27 and 0.23 for EV, SM, LS, AS and SC, respectively. Wide ranges of the EBVs were observed, being -0.69 to 1.27 ml for EV, -18.19 to 11.59% for SM, -19.31 to 9.15% for LS, -2.05 to 6.41% for AS and -0.39 to 0.54 × 109 sperms/ml for SC. The averages of EBV throughout different years of semen collection were ranged from -0.26 to 0.43 ml for EV, -9.73 and 3.32% for SM, -9.99 and 3.45% for LS, -0.65 to 0.53% for AS and -0.19 to 0.13 × 109 sperms per ml for SC. The phenotypic trends plotted throughout the experimental period increased for all semen traits except for EV. The GLSM of the semen phenotypic values were ranged from 3.09 to 3.86 ml for EV, 61.55 and 66.53% for SM, 60.91 and 65.12% for LS, 4.34 to 9.28% for AS and 0.73 to 1.33 × 109 sperms per ml for SC.The differences in generalized least square means among GG, GC and CC genotypes of FSHR gene for semen traits were significantly in favor of GG genotype relative to GC and CC genotypes (P < 0.01). Two genotypes of TC and CC were detected for GH gene and the molecular genetic associations were significantly in favor of CC genotype relative to TC genotype (P < 0.01). Conclusion Enhancing management and feeding practices, the implementation and widespread use of artificial insemination as well as employing precise estimations of predicted breeding values in genetic improvement programs, should effectively enhance the semen traits of Egyptian buffalo bulls. FSHR and GH genes could be used as potential candidate genes for marker-assisted selection to improve semen traits in buffalo bulls.